AN EVALUATION OF VALIDATION CRITERIA ON INTELLIGENT SYSTEM VALIDATION PROCESS - Dyah Sulistyowati Rahayu; Siti Rochimah (Faculty of Computer Science - Universitas Indonesia, 2013)
In the software development cycle, validation is the important stage which is held in final stage especially in intelligent system. Validation obtains the validity, credibility and trustworthy of the system. It is needed to ensure that the intelligent system has same manner as human experts’. Whilst with the importance of validation stage, determining the validation criteria is also important. This paper presents the evaluation of validation criteria which is commonly used in intelligent system validation process. The evaluation is carried out by reviewing the literature of intelligent system validation process. The result shows that the validation criteria have its own characteristic so it requires for understanding the validation criteria characteristics, purposes of validation and also the intelligent system itself to hold validation process.